Young adults diagnosed with high grade gliomas: Patterns of care, outcomes, and impact on employment. (October 2019) - Hafeez, Umbreen; Menon, Siddarth; Nguyen, Bella; Lum, Caroline; Gaughran, Gregory; Pranavan, Ganesalingham; Cher, Lawrence; Nowak, Anna K.; Gan, Hui K.; Parakh, Sagun
Highlights: Limited information on patterns of care of high grade gliomas young adults. Significant impact of diagnosis on employment. Young patients with IDH wild type astrocytomas and GBM have better outcomes. Most patients did not continue in employment post diagnosis. Abstract: There is limited information on the patterns of care and outcomes of high grade gliomas (HGGs) in young adults, in particular, the impact it has on a person's employment. We retrospectively identified young adult patients (age ≤ 40 years old) with newly diagnosed high grade gliomas treated between January 2013 and June 2018 across four major neuro-oncology centres in Australia. Patient demographics, tumour characteristics and treatment parameters were collected and outcomes determined. A total of 113 patients were identified with a median follow up of 27.0 months (range 1.0–70.2 months). The median age was 31 years, majority were male (65%) and employed (71.6%). IDH mutations were detected in 66 (62%) cases. The median progression-free survival (PFS) was 38.0 months (95% CI 23.3–52.7 months) and median overall survival (OS) was not reached. Patients with IDH wild type anaplastic astrocytoma and glioblastoma had a significantly shorter median PFS (19.3 months vs. NR, p = 0.001) and median OS (43.5 months vs NR, p = 0.007) than those with IDH mutated grade III anaplastic astrocytoma and oligodendroglioma. There was no significant difference in median OS or PFS between patients who underwent gross or subtotal tumour resection. Significantly, after diagnosis only 36 (32%) patients reported being employed. Young patients with IDH wild type astrocytomas and glioblastoma had better outcomes than reported historical controls. Most patients did not continue in employment post diagnosis.